PENGARUH KREDIT USAHA RAKYAT (KUR) TERHADAP PENINGKATAN PROFIT USAHA MIKRO PADA NASABAH PT. BANK BUKOPIN CABANG MEDAN SETIA BUDI - Aldillah Dimas Prayogi; Edi Sofian; Faty Rahmarisa (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
The formulation of the problem in this thesis is whether there is an effect of using funds to increase the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch, is there any effect of the amount of credit on increasing the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch, is there any effect of credit burden on increasing the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch, is there any effect of the procedure on increasing the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch. This study aims to determine the effect of the use of funds, the amount of credit, credit burden, and procedures to increase the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch. This type of research is associative research with a quantitative approach. The sample in this study amounted to 69 KUR customers from PT. Bank Bukopin Medan Setia Budi Branch. The analysis technique used is path analysis. The results of this study indicate that the use of funds has no effect on increasing the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch. The amount of credit has a significant positive effect on increasing the profit of micro business customers of PT. Bank Mandiri (Persero) Tbk KCP Medan Wahidin. Credit burden has a significant positive effect on increasing the profit of micro business customers of PT. Bank Bukopin Medan Setia Budi Branch. The procedure has no effect on increasing the profit of micro-business customers of PT. Bank Bukopin Medan Setia Budi Branch.